2006
DOI: 10.1007/1-4020-4927-7
|View full text |Cite
|
Sign up to set email alerts
|

Water and the Cell

Abstract: HB) ISBN-13 978-1-4020-4926-2 (HB) ISBN-10 1-4020-4927-7 (e-book) ISBN-13 978-1-4020-4927-9 (e-book)Published by Springer,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(1 citation statement)
references
References 301 publications
(441 reference statements)
0
1
0
Order By: Relevance
“…The flow of alternating current in the coil makes the impedance of the coil increase, resulting in a change in electrical energy into heat energy. Previous studies reported that treatment with a MFD of 1.2 -3.75 mT, a frequency of 20 Hz, and a treatment time of 5-40 minutes on the water caused a significant temperature increase when the treatment time was 33-37 minutes [25]. Excess heat has the potential to damage the seeds that are being grown.…”
Section: Magnetic Field Treatmentmentioning
confidence: 99%
“…The flow of alternating current in the coil makes the impedance of the coil increase, resulting in a change in electrical energy into heat energy. Previous studies reported that treatment with a MFD of 1.2 -3.75 mT, a frequency of 20 Hz, and a treatment time of 5-40 minutes on the water caused a significant temperature increase when the treatment time was 33-37 minutes [25]. Excess heat has the potential to damage the seeds that are being grown.…”
Section: Magnetic Field Treatmentmentioning
confidence: 99%